Hybrid Fuzzy Sliding Mode Control of a DFIG Integrated into the Network - Belabbas Belkacem; Tayeb Allaoui; Mohamed Tadjine; Ahmed Safa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
This paper presents the study of a variable speed wind energy conversion system using a Doubly Fed Induction Generator (DFIG) based on a Fuzzy sliding mode control (FSMC) applied to achieve control of active and reactive powers exchanged between the stator of the DFIG and the grid to ensure a Maximum Power Point Tracking (MPPT) of a wind energy conversion system. However the principal drawback of the sliding mode, is the chattering effect which characterized by torque ripple, this phenomena is undesirable and harmful for the machines, it generates noises and additional forces of torsion on the machine shaft. In order to reduce the chattering effect, the Sign function of sliding mode controller’s discontinuous part is replaced by a fuzzy logic; we will have the fuzzy sliding mode controller (FSMC). The FSMC makes it possible to combine the performances of the two types of controllers (SMC and FLC) and eliminates the chattering effect. The proposed control algorithm is applied to a DFIG where the stator is directly connected to the grid and the rotor is connected to a three-level converter structure NPC to suppress low level harmonics, higher frequencies will be filtered out by the machine. Second goal of this paper is to extract a maximum of power; the rotor side converter is controlled by using a stator flux-oriented strategy. The decoupling created by the control between active and reactive stator power allows keeping the power factor close to unity. Simulation results show that the wind turbine can operate at its optimum energy for a wide range of wind speed. Both simulation and validation results show effectiveness of the proposed control strategy is in terms of power regulation. Moreover, the fuzzy sliding mode approach is arranged so as to reduce the chattering produced in the generated power that could lead to increased mechanical stress because of strong torque variations.DOI: http://dx.doi.org/10.11591/ijpeds.v3i4.4072